Analisis Pelat Beton Bertulang Bambu Ampel - Moh Lutfi Lukman Mubaroq; Eko Walujodjati (Institut Teknologi Garut, 2022)
Indonesia's need for access to roads and buildings is increasing, but balanced economic growth will not last. Therefore, we are looking for ways to realize light and strong structures at low cost. Bamboo reinforced concrete slabs for traffic lights are an effective combination as an alternative to non-structural plates and members. The Ampel bamboo that will be used is bamboo that is more than one year old, then this bamboo will be shaped to resemble plain iron reinforcement with a diameter of 8mm. Then the test was carried out with a treatment age of 28 days. This study aims to determine the effect of Ampel bamboo on the feasibility of concrete in terms of one-way flexural strength and tensile strength of the Ampel bamboo itself. This research was conducted using theoretical analysis methods with data obtained from the results of laboratory assistants who conducted experiments in the laboratory. From the results of the study it can be concluded that the average tensile strength of Ampel bamboo is 396.10 MPa and meets the standards of plain iron reinforcement, namely a minimum tensile strength of 350 MPa and the flexural strength of concrete slabs obtained by replacing iron reinforcement using Ampel bamboo is 3.64 MPa with a maximum load of 9.07 KN. Also produced ampel bamboo reinforced concrete slab deflection of 0.913 mm.